Governance, Financial Inclusion and Foreign Remittances in Zimbabwe: A VECM Approach - Maune, Alexander; Mundonde, Justice (Acta Universitatis Danubius. Œconomica, 2024)
This study examines the impact of governance and financial inclusion on remittances in Zimbabwe using time series data collected from the World Bank database for the period 2009 to 2021. A vector error correction model was conducted using Stata/SE 14.2 to analyse the short- and long-run relationships between the variables. The results demonstrate the existence of cointegration in the model. The Johansen normalization long-run output showed a negative impact of governance on remittances, as well as a positive impact of financial inclusion on remittances. Both coefficients are statistically significant at the 1% level. Furthermore, the results show that governance and financial inclusion in Zimbabwe have asymmetric effects on remittances in the long run, on average, ceteris paribus. This study is important in policy formulation and implementation. The government should create a conducive environment for remittances through improved governance and financial inclusion policies.